Strategi Guru dalam Meningkatkan Kualitas Mengajar selama Masa Pandemi COVID-19 - Muhammad Yusuf Siregar; Suharian Amiril Akbar (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2020)
The purpose of this study was to determine teacher strategies in improving the quality of teaching during the COVID-19 Pandemic. The research was conducted with a descriptive qualitative method using a naturalistic qualitative approach, data were collected through observation and interviews. The subjects are the principal and teacher. The results showed that online learning made it easier for teachers to transfer information in various situations and conditions because online learning was supported by various platforms ranging from discussions to face-to-face virtually. However, this needs to be evaluated and adjusted to local conditions, given the ability of parents to provide different online learning facilities. The key is to maximize the ability of students to learn in a pandemic like this.